Gestational Exposure to Low Dose Bisphenol A Alters Social Behavior in Juvenile Mice - Wolstenholme, Jennifer T.; Taylor, Julia A.; Shetty, Savera R. J.; Edwards, Michelle; Connelly, Jessica J.; Rissman, Emilie F. (PLOS ONE, 2011)
Bisphenol A (BPA) is a man-made compound used to make polycarbonate plastics and epoxy resins; public health concerns have been fueled by findings that BPA exposure can reduce sex differences in brain and some behaviors. We asked if a low BPA dose, within the range measured in humans, ingested during pregnancy, would affect social behaviors in prepubertal mice. We noted sex differences in social interactions whereby females spent more time sitting side-by-side, while males engaged in more exploring and sitting alone. In addition BPA increased display of nose-to-nose contacts, play solicitations and approaches in both sexes. Interactions between sex and diet were found for self grooming, social interactions while sitting side-by-side and following the other mouse. In all these cases interactions were produced by differences between control and BPA females. We examined brains from embryos during late gestation to determine if gene expression differences might be correlated with some of the sexually dimorphic or BPA affected behaviors we observed. Because BPA treatments ended at birth we took the brains during embryogenesis to increase the probability of discovering BPA mediated effects. We also selected this embryonic age (E18.5) because it coincides with the onset of sexual differentiation of the brain. Interestingly, mRNA for the glutamate transporter, Slc1a1, was enhanced by exposure to BPA in female brains. Also we noted that BPA changed the expression of two of the three DNA methyltransferase genes, Dnmt1 and Dnmt3a. We propose that BPA affects DNA methylation of Sc1a1 during neural development. Sex differences in juvenile social interactions are affected by BPA and in particular this compound modifies behavior in females.